The Effects of Child Care Subsidies on Paid Child Care Participation and Labor Market Outcomes: Evidence from the Child and Dependent Care Credit - Gabrielle Pepin (Institute of Labor Economics (IZA), 2024)
The Child and Dependent Care Credit (CDCC), a tax credit based on income and child care expenses, reduces child care costs for working families. The Economic Growth and Tax Relief Reconciliation Act expanded the CDCC in 2003, generating differential increases in generosity across states and family sizes. Using data from the March Current Population Survey, the author finds that a 100 increase in CDCC generosity increases paid child care participation by 0.6 percentage points among single mothers and 2.2 percentage points among married mothers with children younger than 13 years old. The author also finds that CDCC benefits increase labor supply among married mothers, who may experience long-run earnings gains.
Keywords: J13; H24; J22; H71; 330; child care subsidies; paid child care participation; female labor supply